Stability, phonon calculations, electronic structure, and optical properties of a VO2(M) nanostructure: A comprehensive density functional theory study - Mohebbi, Elaheh; Pavoni, Eleonora; Mencarelli, Davide; Stipa, Pierluigi; Laudadio, Emiliano; Pierantoni, Luca (Frontiers in Materials, 2023)
The aim of this present paper is to precisely consider the physical properties of vanadium dioxide(M), with particular emphasis on optical characteristics. As we discuss here, we employed different exchange-correlation functionals to determine the phase stability, band gap properties and optical characteristics of experimentally recognized monoclinic VO2(M) polymorph. As the matter of fact, the current calculations not only can correctly interpret the origin of VO2(M), but also can generate other optical properties which did not reported with experimental measurement. Phonon dispersion calculations have confirmed that the presence of negative frequencies for acoustic modes in the phonoic curves. While the HSE functional reproduced correctly the experimental band gap, here for the first time, our calculations based on PBE and PBEsol yielded non-zero electronic bandgaps of 0.23 eV and 0.15 eV for bulk VO2(M). Our predictions shown that semi-local functional can adequately predict the semiconductor property of VO2(M) better than all reported previous theoretical works have demonstrated nulled band gap. More importantly, combination of PBEsol/HSE approximation predicted absorption peaks of the imaginary part of the dielectric function in the infrared-visible region with a static dielectric constant 7.54, has displayed excellent match with experiment. The optical reflectivity 22% of VO2(M) computed with HSE hybrid functional in this study revealed remarkably better than most accurate theories like Bethe-Salpeter equation (BSE) and GW approximations by predicted values of 28% and 30%, respectively. Our results propose that the PBEsol + HSE approach efficiently succeed in smart materials characterization for application in electronics and optoelectronics.